Real-world analysis of immunochemotherapy in recurrent small-cell lung cancer: opportunities for second-line approaches - Guo, Yanrong; Han, Songyan; Guo, Qinxiang; Zhai, Jinfang; Ren, Xiaohui; Li, Shengshu; Duan, Jianchun (Frontiers in Pharmacology, 2025)
BackgroundSmall-cell lung cancer (SCLC) has limited therapeutic options beyond first-line treatment, and the efficacy of PD-1/PD-L1-based immunotherapy in this setting remains uncertain. This study evaluates the efficacy and safety of serplulimab-based immunochemotherapy as a second- or later-line treatment for SCLC.MethodsThis retrospective, real-world study included 39 SCLC patients treated with post-initial serplulimab-based immunochemotherapy at Shanxi Provincial Cancer Hospital between May 2022 and November 2023. Primary and secondary endpoints were overall survival (OS) and progression-free survival (PFS), respectively. Cox analyses were conducted to explore factors associated with survival outcomes.ResultsThe median follow-up duration was 13.7 months. The OS was 12.00 months (95% CI: 6.87-not reached), and the median PFS was 4.07 months (95% CI: 3.07–7.17), with an objective response rate of 20.51%. Patients who underwent immunotherapy re-challenge showed numerically higher median OS (12.77 vs. 9.17 months) and PFS (5.93 vs. 3.87 months) than those without prior immunotherapy. Patients with an objective response to front-line therapy exhibited a trend toward improved median OS (not reached vs. 6.47 months) and PFS (5.93 vs. 3.17 months). Cox analysis identified ECOG PS of 2, elevated LDH, ProGrp, and NSE, and liver metastasis were associated with worse OS. The most common adverse events were thrombocytopenia, elevated ALT, and hypothyroidism, with a manageable safety profile.ConclusionSecond- or later-line serplulimab-based immunochemotherapy shows promising antitumor activity and survival benefits for SCLC, regardless of prior immunotherapy exposure. Although limited by sample size and retrospective design, these findings highlight the potential of immunotherapy combinations beyond first-line therapy.